Dantu's mineralogical properties – A view into the composition of Ceres' crust. (27th June 2018) - Stephan, K.; Jaumann, R.; Wagner, R.; De Sanctis, M. C.; Palomba, E.; Longobardo, A.; Williams, D. A.; Krohn, K.; Tosi, F.; McFadden, L. A.; Carrozzo, F. G.; Zambon, F.; et al.
Abstract: Impact crater Dantu not only exhibits a very complex geological history but also shows an exceptional heterogeneity of its surface composition. Because of its location within a low‐lying region named Vendimia Planitia, which has been proposed to represent an ancient impact basin, Dantu possibly offers a window into the composition of Ceres's deeper crust, which apparently is enriched in ammonia. Local concentration of carbonates within Dantu or its ejecta blanket may be either exposed or their emplacement induced by the Dantu impact event. Because carbonates can be seen along Dantu's crater walls, exposed due to recent slumping, but also as fresh spots or clusters of spots scattered across the surface, the deposition/formation of carbonates took place over a long time period. The association of several bright spots enriched in carbonates with sets of fractures on Dantu's floor might be accidental. Nevertheless, its morphological and compositional similarity to the faculae in Ceres's prominent impact crater Occator including its hydrated state does not exclude a cryo‐volcanic origin, i.e., upwelling of carbonate‐enriched brines influenced by H2 O ice in the subsurface. Indeed, an isolated H2 O ice spot can be identified near Dantu, which shows that ice still exists in Ceres's subsurface at midlatitudes and that it can exist on the surface for a longer period of time.